Adaptation Test and Genetic Parameters Estimation of Chili (Capsicum spp.) by Automation Drip Irrigation System in UG Technopark, Cianjur - Dhanussela, Ahmad Ghaly; Istiqlal, Muhammad Ridha Alfarabi; Azmi, Tubagus Kiki Kawakibi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Bean stew efficiency in 2019-2021 is vacillated because of the utilization of improper assortments and ecological variable. This study plans to decide assortments that have ideal development and creation at UG Technopark and to decide the hereditary variety between bean stew assortments. This study used a Randomized Complete Block Design (RCBD) with three blocks and one factor made up of eight chili varieties. The information examination utilized in this review was investigation of varians (ANOVA) at 5 and 1% level and the post hoc test utilized Duncan's Various Reach Test at 5%. Noticed information additionally were broke down utilizing coefficient of hereditary difference, coefficient of phenotypic change and heritability examination. The results showed that the Bonita variety has the highest plant height, dichotomous height, and the largest stem diameter. Bishop's crown variation had the biggest character of crown width, length and width of leaves meanwhile Ayesha variety had the fastest flowering time. On the fruit characters, Bishop’s crown variety had the highest fruit weight per plant and fruit diameter. Reisa varieties had the highest fruit weight. Each character had a wide range of genetic coefficients of variation with values ranging from 16.50 to 77.96%, high phenotypic coefficents of variation with values ranging from 13.93 to 86.38% and high broad meaning heritability values ranging from 0.43 to 1.00.